Extraction resistance of 2.7 mm medio-lateral-placed cortical screws compared with 2.7 mm and 3.5 mm cranio-caudal-placed cortical screws in canine cadaver radii - Linn, L. L.; Rochat, M. C.; Brusewitz, G. H.; Payton, M. E. (Veterinary and Comparative Orthopaedics and Traumatology, 2001)
Medial placement of a 2.7 mm dynamic compression plate (DCP) has been proposed as an alternative to cranial placement of a 3.5 DCP for the treatment of mid-diaphyseal to metaphyseal radial fractures in dogs (13, 17). The purpose of this study was to compare the extraction strength of 2.7 mm screws placed in a medio-lateral (ML) plane with both 2.7 mm and 3.5 mm screws placed in a cranio-caudal (CC) plane in canine cadaver radii.Comparisons between these three screw orientations were evaluated by placing six screws (in vitro) in each of 16 paired radii and then conducting a standard extraction test (also known as a pull-out test). One radius of each pair received 2.7 mm ML screws (n = 48), the opposite radius received either 2.7mm CC or 3.5 mm CC screws (n = 24 each). Extraction strength was compared by screw position within a bone and between planes of placement within matched pairs.Screw position within a bone did not have a significant effect on strength comparisons. The number six (most distal) screw was consistently and significantly weaker than the other screws without regard to plane of placement. Medio-lateral screws were significantly stronger than both 2.7 mm and 3.5 mm screws placed in a cranio-caudal plane. Medial placement of a 2.7 mm dynamic compression plate (DCP) is a viable alternative to cranial placement of a 3.5 DCP for treatment of mid-diaphyseal to distal radial fractures in dogs, with regard to screw purchase and holding strength.A comparison of extraction strength of 2.7 mm screws placed in a medio-lateral (ML) plane was made with both mm and 3.5 mm screws placed in a cranio-caudal (CC) plane in canine cadaver radii. Medio-lateral screws were significantly stronger than both mm and 3.5 mm screws placed in a cranio-caudal plane. With regard to screw purchase and holding strength, medial placement of a 2.7 mm dynamic compression plate (DCP) is a viable alternative to cranial placement of a 3.5 DCP for treatment of mid-diaphyseal to distal radial fractures in dogs.
Keywords: Extraction; cortical screws; placement; canine